Empowering Whistleblowers: Strengthening Corporate Fraud Detection and Financial Integrity in Sri Lanka through Comprehensive Legal Protections - Nanayakkara, W.I. (My University, 2024)
Whistleblowing refers to the act of reporting illegal, fraudulent or unethical activities within an organization to the appropriate authorities. Whistleblowing was previously limited to the public sector, but has now extended to the corporate sector. This expansion is a result of recognizing the significant and widespread consequences of corporate fraud on the general public. Whistleblowers are vital in the fight against corporate fraud and financial crimes, thereby preventing further harm and holding the perpetrators accountable. They play a crucial role in uncovering unethical practices and exposing financial wrongdoing, acting as a necessary safeguard for corporate integrity and accountability. This paper explores the effectiveness of whistleblowers in detecting and preventing corporate fraud, using global examples to highlight the significance of robust frameworks and protective measures. In countries like the United States and the United Kingdom, where comprehensive whistleblower protection laws exist, whistleblowers have made significant contributions to uncovering fraudulent activities, resulting in promoting transparency and corporate governance. The current laws in Sri Lanka lack adequate provisions for whistleblowing and fail to effectively protect whistleblowers, which hinders the fight against corporate fraud. This study employs library research to gather primary and secondary qualitative data from statutes, case studies, books, and journal articles with a comparative approach to the United States and the United Kingdom to suggest effective whistleblowing mechanisms and legal frameworks to help prevent fraud in Sri Lanka. ...
Keywords: Whistleblowing; Corporate Fraud; Financial Integrity; Legal Protections